The effect of workstress towards work-life balance among employees in Baling / Nur Ain Azizan - Azizan, Nur Ain (2019)
Work-life balance is very important among the employees. This research study has been conducted to examine factors that influencing work-life balance. The independent variables that include in this research study are workload, role conflict and interpersonal relationship. By conducting this research study, researcher will identify whether the independent variable related to the work-life balance. The total 97 set of questionnaire have been prepared and will be distribute to the respondent. The respondent are from the employees who are working in Baling, Kedah. Further, Statistical Package for the Social Sciences (SPSS) version 23 will be used to calculate the data from the questionnaire. In the end, the results will be reveal after all the data successfully collected from the respondent and calculate precisely.